Effect of replacing wheat with broken rice on nutrients metabolisability, egg production and quality in White Pekin ducks - NAIK, P K; SWAIN, B K; SAHOO, S K; KUMAR, D; MISHRA, S K; BEURA, C K (The Indian Journal of Animal Sciences, 2022)
A study was conducted in the tropical coastal region of Odisha in 2019 to find out the effect of replacing wheat with broken rice (BR) on nutrients metabolisability, egg production and quality in White Pekin ducks. White Pekin ducks (45, 165 days) were divided into three groups with three replicates in each group and each replicate had five ducks. Three experimental diets without (BR-0) and with BR, replacing 50 (BR-50) and 100 (BR-100), per cent wheat were prepared. The above diets were offered randomly to the groups till 40 weeks followed by conduction of a metabolic trial. The dry matter intake (g/d) was similar among the groups. The metabolisability percentage of dry matter, organic matter, crude protein, ether extract and crude fibre in BR-0 and BR-50 were similar and higher than BR-100. There was no significant difference in N balance (g/d) among the groups. The total egg production, duck day egg production percentage and feed conversion ratio were similar among the groups. The external and internal egg quality parameters were similar among the groups as well. It was concluded that wheat can be replaced with broken rice at 50% level in the diets of White Pekin ducks during first phase of laying under intensive rearing system with increase in the metabolisability of the nutrients of the feed without affecting the performance.